Students’ Perception of Mind Mapping in Learning Vocabulary - Juwita Crestiani M; Opik Dwi Indah; Hermini Hermini (Universitas Cokroaminoto Palopo, 2022)
This research deals with the sixth year students’ perception of mind mapping in learning vocabulary at PalopoCokroaminoto University. The population of this research was the primary school teacher education study program in PalopoCokroaminoto University in academic year 2021/2022. The total number of population was 10 students. The researcher used the purposive sampling. Based on the findings and discussion in the previous chapter, the researcher concludes that the English students give positive perception mind mapping in PalopoCokroaminoto University. It is supported by students’ answer about mind mapping that “mind mapping is good and appropriate to be used in learning vocabulary.